2010
DOI: 10.1007/s00586-010-1420-z
|View full text |Cite
|
Sign up to set email alerts
|

Late-onset post-diskectomy tuberculosis at the same operated lumbar level: case report and review of literature

Abstract: Late post-diskectomy tuberculous spondylodiskitis at the operated level is an extremely rare phenomenon. We describe a unique case of a same level tuberculous spondylodiskitis with pus drainage from the operative scar 8 years after simple L4/L5 diskectomy and review the relevant literature. The therapeutic management and possible pathogenic mechanisms are discussed as well.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 39 publications
(80 reference statements)
0
5
0
Order By: Relevance
“…Two of these reported cases were diagnosed three months after the index procedure [25,26]. Lotfinia et al [15] reported a case in 2010 of late-onset postdiscectomy tuberculosis at the same lumbar level eight years after simple L4-L5 discectomy. The features of this disc tuberculosis infection are the difficulty of diagnosis, with nonspecific clinical signs and culture and the duration of the treatment.…”
Section: Postoperative Tuberculosis Spondilodiscitismentioning
confidence: 99%
See 1 more Smart Citation
“…Two of these reported cases were diagnosed three months after the index procedure [25,26]. Lotfinia et al [15] reported a case in 2010 of late-onset postdiscectomy tuberculosis at the same lumbar level eight years after simple L4-L5 discectomy. The features of this disc tuberculosis infection are the difficulty of diagnosis, with nonspecific clinical signs and culture and the duration of the treatment.…”
Section: Postoperative Tuberculosis Spondilodiscitismentioning
confidence: 99%
“…High rates of infection have been observed in elderly patients and spine trauma patients [13][14]. Obesity has also been quoted as a risk factor by many [15][16][17].…”
Section: Incidencementioning
confidence: 99%
“…In our series Mycobacterium tuberculosis (MTB) was present in 1 case. Three cases of POS due to MTB are reported in English literature [51][52][53]. It was noted that the cases of MTB culture-positive cases in our series were operated at rural centers for the index LDH surgery, based on poor quality MRI images of 0.5 Tesla machines.…”
Section: Discussionmentioning
confidence: 96%
“…Late-onset spondylodiscitis and psoas abscess 5 years after percutaneous balloon kyphoplasty have been reported [11]. Late tuberculous spondylodiscitis 8 years after discectomy was described by Lotfinia and Vahedi [12]. Besides these long duration periods; no case of spondylodiscitis 9 years after posterior spine surgery has been described so far.…”
Section: Discussionmentioning
confidence: 99%